Animal milk, a miracle food or a real poison ? - Larbi OUSSADOU; Louiza DJERDJAR (Journal de la Faculté de Médecine d'Oran, 2022)
Animal milk is widely consumed in the world, its composition in macro and micronutrient, its availability have made it a key element in the basic diet of individuals. Between anti-milk speeches and those who present it as a miracle food, the liquid is the subject of many controversies. This article reviews the debate about the health effects of consuming animal milk and its derivatives.